Breadsticks with enhanced nutritional value for salt-free nutrition - Krivosheev A.; Lukina S.; Alekhina N.; Gabelko Y.; Agapov B. (Техника и технология пищевых производств)
At present moment it is essential to produce food which not only satisfies people’s needs, but also has a particular nutritional value and vitamin and mineral content. Introduction of non-traditional types of plant materials in the recipes of baked goods for preventive and therapeutic nutrition is a promising direction for enhancing their nutritional value. Consumption of these products improves the balance of vitamins, amino acids, trace elements, macronutrients, food fibers and has a positive effect on human health. The article presents the development of breadstick recipe for salt-free nutrition using flax seed flour and grapeseed oil which guarantee overall enrichment of food recommended in case of such diseases as heart and renal failure, hypertension, osteoporosis, arthritis and arthrosis. Using flax seed flour in baked goods production will make it possible to increase the content of protein, food fibers, vitamins and mineral substances in them. Grapeseed oil has a lot of polyunsaturated fatty acids and biologically active substances which improve immune barrier. The article reveals the results of the determination of the table salt effect as well as the influence of non-traditional types of raw materials on organoleptic, physical and chemical parameters of the ready-to-use products, their microstructure and antioxidant activity. The author suggests using enzymatic composition instead of table salt in breadsticks recipe for salt-free nutrition. The article presents the results of the chemical composition determination and calculation of breadsticks nutritional value. The obtained data will help extend the product line of special-use baked goods with higher nutritional value.